Succesfully planning for SOA taking a strategic approach to realizing SOA. - Groves, David
As you continue to develop your IT architecture, it becomes clear that the route to achieving real business benefits requires a fundamental change in the way you think about system design. In this article on services-oriented architecture (SOA), I'll share with you helpful tips, insights and a domain model to help you plan this change and ensure the success of your SOA implementation.